Copper-based composite current collector, preparation method thereof and application of copper-based composite current collector in negative-electrode-free metal battery
By constructing a copper sulfide modification layer on the copper-based current collector of the negative electrode-free sodium metal battery, the problems of disordered deposition of sodium/magnesium ions and dendrites under high current and high surface capacity are solved, and high Coulombic efficiency and excellent cycle life are achieved.
Patent Information
- Application Number
- CN202411792711.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-07
- Publication Date
- 2025-03-21
AI Technical Summary
The existing negative electrode-free sodium metal batteries have problems such as disordered deposition of sodium/magnesium ions, dendrite growth and SEI film rupture under high current and high surface capacity, resulting in poor battery cycle life and safety hazards.
Using a copper-based composite fluid modified by copper sulfide, a linear copper sulfide layer with a diameter of 0.05-1 μm is formed on the surface of the copper foil by electroless plating to form a CuS layer with sodium philological characteristics.
The current collector effectively promotes the uniform distribution of sodium ions, regulates the uniform nucleation and stable growth of sodium metals, inhibits dendrites, and improves the balun efficiency and cycle life of the battery.
Smart Images

Figure CN119674090A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of battery materials and relates to a negative electrode-free metal battery. Background Art
[0002] Sodium-ion batteries (SIBs) are becoming a strong competitor to lithium-ion batteries (LIBs) in the secondary battery market due to their high resource abundance and good economic benefits. However, due to the limited choice of negative electrode materials, the best performing sodium-ion batteries can only provide 120-160 Wh kg -1 The energy density of the battery is only the lowest standard of LiFePO4 series lithium-ion batteries. When the negative electrode is eliminated and an ultra-thin copper current collector is used to match the high-voltage positive electrode, the negative electrode-free sodium metal battery (AFSIB) is expected to achieve more than 300 Wh kg -1 The high energy density of the material can further expand its application in electric vehicles, thin and light electronic devices and other fields.
[0003] The reaction on the negative electrode side of the negative electrode metal battery changes from the insertion / deinsertion of metal ions to the deposition / stripping of metal ions. However, the traditional copper and aluminum foil current collectors have low affinity for sodium metal, which leads to the continuous growth of dead sodium and dendrite sodium and the formation of unstable solid electrolyte interface (SEI), which in turn causes low coulombic efficiency of the battery. Especially under high current density and high capacity load conditions, poor affinity between metal and current collector will greatly reduce the cycle life of the battery and cause a series of safety issues, such as dendrites piercing the diaphragm and excessive consumption of electrolyte to produce gas. Therefore, the development of a new type of current collector with affinity for metal is of great significance for inducing uniform metal deposition and achieving high energy density negative electrode metal batteries.
[0004] Existing articles and technologies have reported some negative electrode-free sodium metal batteries. For example, Wang et al. prepared a composite current collector by spraying CuSb2 alloy on copper foil by magnetron sputtering to improve the sodium affinity of the current collector surface. However, since this modification method cannot well control the particle size of the surface modification layer, it cannot be stably cycled under high current density and high surface capacity. In addition, Liu et al. constructed a Cu3P modification layer on the surface of copper foil by high-temperature calcination to provide more sites for sodium deposition. However, the maximum current achieved was not ideal, only 4 mA cm -2 The current density was cycled for about 500 h, and the calcination process was relatively time-consuming for the preparation of the current collector. Although the application with publication number CN 117878259 A discloses a method for preparing a negative electrode current collector for a negative electrode-free sodium ion battery, it adopts a sulfur deposition method. Figure 4It can be seen that the negative electrode current collector of the negative electrode-free sodium ion battery is still used as the negative electrode for electrochemical testing. It can be inferred that the CuS of the negative electrode current collector is relatively thick and still plays the role of the negative electrode, which is not considered a negative electrode-free battery. In order to further explore the preparation process of negative electrode-free metal batteries, this application has conducted in-depth exploration. Summary of the invention
[0005] Aiming at the problems of disordered deposition of sodium / magnesium ions, growth of sodium / magnesium dendrites, and rupture of SEI film due to volume expansion under high current and high surface capacity, which lead to poor battery cycle life under actual working conditions, the present invention proposes a copper-based composite current collector, a preparation method thereof, and an application thereof in a negative electrode-free metal battery.
[0006] The technical solution of the present invention is achieved in this way: A copper-based composite current collector modified with copper sulfide comprises a copper foil and a copper sulfide modification layer. The copper sulfide modification layer is a copper sulfide having a linear structure with a diameter of 0.05-1 μm constructed in situ on the surface of the copper foil. The thickness of the copper sulfide modification layer is 0.5-5 μm.
[0007] The preparation method of the copper-based composite current collector modified by copper sulfide is as follows: (1) After pretreatment, the copper foil is placed in an acid solution to remove impurities on the surface of the copper foil; (2) Depositing a copper sulfide modification layer by chemical plating: dissolving sodium sulfide or potassium sulfide in deionized water to prepare a sodium sulfide solution or a potassium sulfide solution, then immersing the copper foil pretreated in step (1) in the sodium sulfide solution or the potassium sulfide solution, and then washing with deionized water. After repeating the immersion-washing process 2-5 times, the copper-based composite current collector modified with copper sulfide is obtained after drying.
[0008] The pretreatment in the above step (1) includes copper foil drying treatment and acid solution treatment.
[0009] The above-mentioned pretreatment is to dry the copper foil at 60°C for 1-12 hours to remove moisture; the acidic solution is 0.1-1.5 M HCl, H2SO4, CH3COOH solution, and the treatment time is 2-20 seconds to remove oxidized impurities on the surface of the copper foil.
[0010] The concentration of sodium sulfide or potassium sulfide in the sodium sulfide or potassium sulfide solution in the above step (2) is 0.002-0.010 g / mL.
[0011] In the above step (2), the immersion time in the sodium sulfide or potassium sulfide solution is 10-300 s.
[0012] Application of the above copper sulfide modified copper-based composite current collector in negative electrode-free sodium / magnesium metal batteries.
[0013] A sodium metal battery without a negative electrode comprises a positive electrode sheet, an electrolyte, a diaphragm and the copper-based composite current collector modified by copper sulfide.
[0014] The above-mentioned negative electrode-free sodium / magnesium metal battery can be in the form of a button or a soft pack.
[0015] Furthermore, the positive electrode sheet comprises a positive electrode active material, a conductive agent and a binder; and the electrolyte comprises a sodium salt and an organic solvent.
[0016] Furthermore, the positive electrode active material of the sodium metal battery is any one of sodium vanadium phosphate, sodium iron pyrophosphate, sodium iron pyrophosphate, and sodium iron manganese pyrophosphate; the positive electrode material of the magnesium metal battery is MgCrMnO4 or MgV2O4; the conductive agent is graphene, carbon nanotubes, acetylene black, Ketjen black or Super P Li; the binder is polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE); the sodium salt is any one or more of sodium hexafluorophosphate, sodium perchlorate, sodium trifluoromethanesulfonate, sodium tetrafluoroborate, sodium bis(fluorosulfonyl)imide and sodium bis(trifluoromethylsulfonyl)imide; the magnesium salt is Mg(TFSI)2 or Mg(SO3CF3)2; the organic solvent is any one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, diethylene glycol dimethyl ether, 1,3-cyclopentanediol, ethylene glycol dimethyl ether and triethylene glycol dimethyl ether; the diaphragm is any one of polyethylene, polypropylene microporous membrane, glass fiber membrane and polyacrylonitrile diaphragm.
[0017] The positive electrode active material of the negative electrode-free magnesium metal battery is MgCrMnO4 or MgV2O4; the binder is polyvinylidene fluoride or polytetrafluoroethylene; the magnesium salt is Mg(TFSI)2 or Mg(SO3CF3)2; the organic solvent is tetrahydrofuran and / or ethylene glycol dimethyl ether; the conductive agent is any one or more of graphene, carbon nanotubes, acetylene black, Ketjen black and Super P Li; the diaphragm is any one of polyethylene, polypropylene microporous membrane, glass fiber membrane and polyacrylonitrile diaphragm.
[0018] The preparation method of the above-mentioned negative electrode-free sodium / magnesium metal battery comprises the following steps: (1) The positive electrode active material, binder, and conductive agent were dissolved in N-methylpyrrolidone solvent at a mass ratio of 8:1:1 and stirred evenly to prepare a slurry. The slurry was applied on the current collector and dried overnight at 120°C in vacuum. The slurry was then cut into 12 mm pole pieces with a pole piece loading of 12 mg cm. -2 Making a positive electrode sheet; (2) Cut the copper-based composite current collector modified with copper sulfide into discs with a diameter of 16 mm (diameter 16 mm), separate the electrode from the positive electrode with a separator, and drip electrolyte (concentration 1 M). Use CR2025 stainless steel shell as the battery shell to assemble into a button battery.
[0019] The present invention has the following beneficial effects: (1) The present invention synthesizes a composite current collector of a negative electrode-free sodium metal battery with a highly ordered copper sulfide layer on the current collector through a simple chemical plating process. Through a simple liquid-solid phase reaction: xNa2S + 2yCu → 2NaxCuyS (Na2S@CuS), an ultra-thin (0.5-5 μm) CuS layer with sodium-philic properties is in situ generated on the copper current collector. The biggest advantage of this method is that it can be prepared in large quantities without the need for cumbersome steps such as calcination. The interface layer was characterized by SEM-EDS technology and found to have a Na content of 1.49 wt% and a S content of 0.55 wt%, proving that the CuS content on the copper foil is extremely small (it cannot be used as a negative electrode material and cannot provide effective capacity), and only exhibits current collector characteristics. The preparation process does not involve multiple coatings, so it is simple, highly homogenized, environmentally friendly and safe, and can be prepared and applied on a large scale.
[0020] (2) The present invention designs a new type of copper-based composite current collector (CuS / Cu) modified by copper sulfide for a negative electrode-free sodium metal battery. The sodium-philic sulfide layer effectively promotes the uniform distribution of sodium ions on the copper-based composite current collector modified by copper sulfide. The current collector of the present application is more compact on the original morphology of the copper foil, rather than the morphology of CuS covering the morphology of the copper foil. The uniform nucleation and subsequent stable growth of sodium metal are regulated, and the growth of dendrites is inhibited to buffer the volume expansion. When the copper-based composite current collector modified by copper sulfide is applied to a negative electrode-free sodium metal battery, high coulombic efficiency and excellent cycle life are achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 Optical images of the unmodified copper foil of Comparative Example 1 (left picture) and the CuS / Cu-30 prepared in Example 1 of the present invention (right picture).
[0023] Figure 2 This is the X-ray diffraction (XRD) pattern of CuS / Cu-30 prepared in Example 1 of the present invention.
[0024] Figure 3 This is a scanning electron microscope (SEM) image of CuS / Cu-30 prepared in Example 1 of the present invention.
[0025] Figure 4 This is a scanning electron microscope-energy dispersive spectrometer (SEM-EDS) image of the cross section of CuS / Cu-30 prepared in Example 1 of the present invention.
[0026] Figure 5 The battery performance test of the half-cell assembled by CuS / Cu prepared in Examples 1-8 of the present invention and the unmodified copper foil of Comparative Example 1; wherein a is the battery performance test of the half-cell assembled by CuS / Cu prepared in Examples 1-8 of the present invention and the unmodified copper foil of Comparative Example 1 at 2 mA cm -2 The current density and 2 mAh cm -2 Reversibility and cycle life test of electroplating and stripping under the condition of sodium deposition amount of 2 mA cm -2 (2 mAh cm -2 ) under the deposition conditions of 1, 10, and 20 weeks of sodium deposition.
[0027] Figure 6 The symmetric battery assembled with the negative electrode-free sodium metal battery composite current collector prepared in Example 1 of the present invention and the unmodified copper foil of Comparative Example 1 was tested at 4 mA cm -2 The current density and 4 mAh cm -2 Dendrite suppression and cycle life testing of areal capacity.
[0028] Figure 7 The cycle performance curve of the negative electrode-free sodium metal full battery assembled with the copper-based composite current collector modified with copper sulfide prepared in Example 1 and the unmodified copper foil of Comparative Example 1.
[0029] Figure 8 The negative electrode-free magnesium metal battery assembled with the copper-based composite current collector modified with copper sulfide prepared in Example 1 was tested at 1 mA cm -2 and 1 mAh cm -2 The charge and discharge curves of the 1st, 5th, 10th, 15th and 20th weeks under the same conditions.
[0030] Fig. 9 The negative electrode-free magnesium metal battery assembled with the copper-based composite current collector modified with copper sulfide prepared in Example 1 was tested at 1 mA cm -2 and 1 mAh cm -2 Time voltage curve under the condition.
[0031] Fig.10 The negative electrode-free magnesium battery assembled with the copper-based composite current collector modified with copper sulfide prepared in Example 1 was tested at 1 mA cm -2 and 1 mAh cm-2 Coulomb efficiency diagram under . DETAILED DESCRIPTION
[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0034] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0035] A copper-based composite current collector modified with copper sulfide comprises a copper foil and a copper sulfide modification layer. The copper sulfide modification layer is a copper sulfide having a linear structure with a diameter of 0.05-1 μm in situ constructed on the surface of the copper foil. The thickness of the copper sulfide modification layer is 0.5-5 μm.
[0036] The preparation method of the copper-based composite current collector modified by copper sulfide is as follows: (1) After pretreatment, the copper foil is placed in an acid solution to remove impurities on the surface of the copper foil; (2) Depositing a copper sulfide modification layer by chemical plating: dissolving sodium sulfide or potassium sulfide in deionized water to prepare a sodium sulfide solution or a potassium sulfide solution, then immersing the copper foil pretreated in step (1) in the sodium sulfide solution or the potassium sulfide solution, and then washing with deionized water. After repeating the immersion-washing process 2-5 times, the copper-based composite current collector modified with copper sulfide is obtained after drying.
[0037] The pretreatment in the above step (1) includes copper foil drying treatment and acid solution treatment.
[0038] The above-mentioned pretreatment is to dry the copper foil at 60°C for 1-12 hours to remove moisture; the acidic solution is 0.1-1.5 M HCl, H2SO4, CH3COOH solution, and the treatment time is 2-20 seconds to remove oxidized impurities on the surface of the copper foil.
[0039] The concentration of sodium sulfide or potassium sulfide in the sodium sulfide or potassium sulfide solution in the above step (2) is 0.002-0.010 g / mL.
[0040] In the above step (2), the immersion time in the sodium sulfide or potassium sulfide solution is 10-300 s.
[0041] Application of the above copper sulfide modified copper-based composite current collector in negative electrode-free sodium / magnesium metal batteries.
[0042] A sodium metal battery without a negative electrode comprises a positive electrode sheet, an electrolyte, a diaphragm and the copper-based composite current collector modified by copper sulfide.
[0043] The above-mentioned negative electrode-free sodium / magnesium metal battery can be in the form of a button or a soft pack.
[0044] Furthermore, the positive electrode sheet comprises a positive electrode active material, a conductive agent and a binder; and the electrolyte comprises a sodium salt and an organic solvent.
[0045] Furthermore, the positive electrode active material is any one of sodium vanadium phosphate, sodium iron pyrophosphate, sodium iron pyrophosphate and sodium iron manganese pyrophosphate. For example, the positive electrode active material is sodium vanadium phosphate; the positive electrode active material is sodium iron pyrophosphate; the positive electrode active material is sodium iron pyrophosphate; the positive electrode active material is sodium iron manganese pyrophosphate.
[0046] Furthermore, the conductive agent is any one or more of graphene, carbon nanotubes, acetylene black, Ketjen black or Super P Li. For example, the conductive agent is graphene; the conductive agent is carbon nanotubes; the conductive agent is acetylene black; the conductive agent is Super P Li.
[0047] Furthermore, the binder is polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE). For example, the binder is polyvinylidene fluoride; the binder is polytetrafluoroethylene.
[0048] Further, the sodium salt is any one or more of sodium hexafluorophosphate, sodium perchlorate, sodium trifluoromethanesulfonate, sodium tetrafluoroborate, sodium bis(fluorosulfonyl)imide and sodium bis(trifluoromethylsulfonyl)imide. For example, the sodium salt is sodium hexafluorophosphate; the sodium salt is sodium perchlorate; the sodium salt is sodium trifluoromethanesulfonate; the sodium salt is sodium tetrafluoroborate; the sodium salt is sodium bis(fluorosulfonyl)imide; the sodium salt is sodium bis(trifluoromethylsulfonyl)imide.
[0049] Further, the organic solvent is any one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, diglyme, 1,3-cyclopentanediol, ethylene glycol dimethyl ether and triethylene glycol dimethyl ether. For example, the organic solvent is ethylene carbonate; the organic solvent is propylene carbonate; the organic solvent is dimethyl carbonate; the organic solvent is diethyl carbonate; the organic solvent is diglyme; the organic solvent is 1,3-cyclopentanediol; the organic solvent is ethylene glycol dimethyl ether; the organic solvent is triethylene glycol dimethyl ether.
[0050] Furthermore, the above-mentioned diaphragm is any one of polyethylene, polypropylene microporous membrane, glass fiber membrane and polyacrylonitrile diaphragm. For example, the diaphragm is polyethylene; the diaphragm is polypropylene microporous membrane; the diaphragm is glass fiber membrane; the diaphragm is polyacrylonitrile diaphragm.
[0051] Example 1 The preparation method of a copper-based composite current collector modified by copper sulfide in this embodiment comprises the following steps: Step 1: First, the copper foil was dried in an oven for 3 h and then immersed in 1 M HCl solution for 5 s to remove the oxidized impurities on the surface of the Cu foil.
[0052] Step 2: Prepare the sulfide plating solution by dissolving 0.5 g Na2S in 100 mL H2O.
[0053] Step 3: The copper foil treated in step 1 is then immersed in deionized water for 30 s to remove the acidic substances on the surface of the copper foil, and then immersed in a sulfide plating solution for 30 s. Finally, it is repeatedly immersed and washed twice with deionized water to deposit a uniform CuS layer on the Cu surface. The thickness of the copper sulfide modification layer is 2 μm.
[0054] Step 4: Dry the CuS / Cu-30 material obtained in step 3 at 60°C for 6 h, and then obtain a copper-based composite current collector modified with copper sulfide for a negative electrode-free sodium metal battery.
[0055] The invention has a simple manufacturing method and is easy to mass produce. Figure 1 This is an optical image (18.5 cm×14 cm) of a copper current collector modified with copper sulfide (Example 1) produced in large quantities by chemical plating. The CuS / Cu-30 prepared in Example 1 was subjected to XRD test. Figure 2 As shown in Figure 2, the copper-based composite current collector modified with copper sulfide is mainly composed of two elements, Cu and S. The (105) and (207) crystal planes are the main exposed crystal planes of copper sulfide after chemical plating. Figure 3 ), the original morphology of the copper foil is more dense, and the morphology of the non-CuS covers the morphology of the copper foil. The copper sulfide with nanorod-like structure is evenly distributed on the copper substrate. Figure 4 , SEM-EDS test results are shown in Table 1: Table 1 SEM-EDS test table The copper sulfide modified layer (interface layer) was characterized by SEM-EDS technology and found to have a Na content of 1.49 wt% and a S content of 0.55 wt%, proving that the CuS content on the copper foil is extremely low. The thickness of the copper sulfide modified layer is about 2 μm (it cannot be used as a negative electrode material and cannot provide effective capacity), and it only exhibits current collector characteristics.
[0056] Example 2 The preparation method of a copper-based composite current collector modified by copper sulfide in this embodiment comprises the following steps: Step 1: First, the copper foil was dried in an oven for 3 h and then immersed in 1 M HCl solution for 5 s to remove the oxidized impurities on the surface of the Cu foil.
[0057] Step 2: Prepare the sulfide plating solution by dissolving 0.5 g Na2S in 100 mL H2O.
[0058] Step 3: The copper foil treated in step 1 is then immersed in deionized water for 30 seconds to remove the acidic substances on the surface of the copper foil, and then immersed in a sulfide plating solution for 10 seconds, and finally repeatedly immersed and cleaned with deionized water twice to deposit a uniform CuS layer on the Cu surface.
[0059] Step 4: The CuS / Cu-10 material obtained in step 3 is dried at 60°C for 6 h, and then a copper-based composite current collector modified with copper sulfide for a negative electrode-free sodium metal battery is obtained.
[0060] Example 3 The preparation method of a copper-based composite current collector modified by copper sulfide in this embodiment comprises the following steps: Step 1: First, the copper foil was dried in an oven for 3 h and then immersed in 1 M HCl solution for 5 s to remove the oxidized impurities on the surface of the Cu foil.
[0061] Step 2: Prepare the sulfide plating solution by dissolving 0.5 g Na2S in 100 mL H2O.
[0062] Step 3: The copper foil treated in step 1 is then immersed in deionized water for 30 seconds to remove the acidic substances on the surface of the copper foil, and then immersed in a sulfide plating solution for 60 seconds, and finally repeatedly immersed and cleaned with deionized water twice to deposit a uniform CuS layer on the Cu surface.
[0063] Step 4: The CuS / Cu-20 material obtained in step 3 is dried at 60°C for 6 h, and then a copper-based composite current collector modified with copper sulfide for a negative electrode-free sodium metal battery is obtained.
[0064] Example 4 The preparation method of a copper-based composite current collector modified by copper sulfide in this embodiment comprises the following steps: Step 1: First, the copper foil was dried in an oven for 3 h and then immersed in 1 M HCl solution for 5 s to remove the oxidized impurities on the surface of the Cu foil.
[0065] Step 2: Prepare the sulfide plating solution by dissolving 0.5 g Na2S in 100 mL H2O.
[0066] Step 3: The copper foil treated in step 1 is then immersed in deionized water for 30 seconds to remove the acidic substances on the surface of the copper foil, and then immersed in a sulfide plating solution for 120 seconds, and finally repeatedly immersed and cleaned with deionized water twice to deposit a uniform CuS layer on the Cu surface.
[0067] Step 4: The CuS / Cu-40 material obtained in step 3 is dried at 60°C for 6 h, and then a copper-based composite current collector modified with copper sulfide for a negative electrode-free sodium metal battery is obtained.
[0068] Example 5 The preparation method of a copper-based composite current collector modified by copper sulfide in this embodiment comprises the following steps: Step 1: First, the copper foil was dried in an oven for 3 h and then immersed in 1 M HCl solution for 5 s to remove the oxidized impurities on the surface of the Cu foil.
[0069] Step 2: Prepare the sulfide plating solution by dissolving 0.5 g Na2S in 100 mL H2O.
[0070] Step 3: The copper foil treated in step 1 is then immersed in deionized water for 30 seconds to remove the acidic substances on the surface of the copper foil, and then immersed in a sulfide plating solution for 180 seconds, and finally repeatedly immersed and cleaned with deionized water twice to deposit a uniform CuS layer on the Cu surface.
[0071] Step 4: Dry the CuS / Cu-50 material obtained in step 3 at 60°C for 6 h, and then obtain a copper-based composite current collector modified with copper sulfide for a negative electrode-free sodium metal battery.
[0072] Example 6 The preparation method of a copper-based composite current collector modified by copper sulfide in this embodiment comprises the following steps: Step 1: First, the copper foil was dried in an oven for 3 h and then immersed in 1 M HCl solution for 5 s to remove the oxidized impurities on the surface of the Cu foil.
[0073] Step 2: Prepare the sulfide plating solution by dissolving 0.5 g Na2S in 100 mL H2O.
[0074] Step 3: The copper foil treated in step 1 is then immersed in deionized water for 30 seconds to remove the acidic substances on the surface of the copper foil, and then immersed in a sulfide plating solution for 300 seconds, and finally repeatedly immersed and cleaned with deionized water twice to deposit a uniform CuS layer on the Cu surface.
[0075] Step 4: The CuS / Cu-60 material obtained in step 3 is dried at 60° C. for 6 h, and then a copper-based composite current collector modified with copper sulfide for a negative electrode-free sodium metal battery is obtained.
[0076] Example 7 The preparation method of a copper-based composite current collector modified by copper sulfide in this embodiment comprises the following steps: Step 1: First, the copper foil was dried in an oven for 3 h and then immersed in 1 M HCl solution for 5 s to remove the oxidized impurities on the surface of the Cu foil.
[0077] Step 2: Prepare the sulfide plating solution by dissolving 1.0 g Na2S in 100 mL H2O.
[0078] Step 3: Then, immerse the copper foil treated in step 1 in deionized water for 30 seconds to remove the acidic substances on the surface of the copper foil, and then immerse it in sodium sulfide solution for 30 seconds, and finally repeat the immersion-washing with deionized water twice to deposit a uniform CuS layer on the Cu surface.
[0079] Step 4: The CuS / Cu-20-1 material obtained in step 3 is dried at 60°C for 6 h, and then a copper-based composite current collector modified with copper sulfide for a negative electrode-free sodium metal battery is obtained.
[0080] Example 8 The preparation method of a copper-based composite current collector modified by copper sulfide in this embodiment comprises the following steps: Step 1: First, the copper foil was dried in an oven for 3 h and then immersed in 1 M HCl solution for 5 s to remove the oxidized impurities on the surface of the Cu foil.
[0081] Step 2: Prepare the sulfide plating solution by dissolving 0.2 g Na2S in 100 mL H2O.
[0082] Step 3: The copper foil treated in step 1 is then immersed in deionized water for 30 seconds to remove the acidic substances on the surface of the copper foil, and then immersed in a sulfide plating solution for 30 seconds, and finally repeatedly immersed and cleaned with deionized water twice to deposit a uniform CuS layer on the Cu surface.
[0083] Step 4: The CuS / Cu-20-0.2 material obtained in step 3 is dried at 60°C for 6 h, and then a copper-based composite current collector modified with copper sulfide for a negative electrode-free sodium metal battery is obtained.
[0084] Comparative Example 1 In this comparative example, no modification layer is applied to the copper foil current collector, and the bare copper foil is directly used as the current collector of the negative electrode-free sodium metal battery, and the thickness of the Cu foil is 12 μm.
[0085] Implementation effect example The copper-based composite current collector modified with copper sulfide prepared in Examples 1-8 was used as the working electrode and sodium metal was used as the counter electrode to assemble button cells (half-cells), and the coulombic efficiency and cycle stability of the half-cells were tested. The specific process of assembling the half-cells and testing their performance is as follows: (1) The copper-based composite current collector modified with copper sulfide prepared in Examples 1-8 was dried at 60° C. in a vacuum oven and then cut into working electrode pieces with a diameter of 16 mm.
[0086] (2) Sodium metal sheet is used as the counter electrode (12 mm in diameter), double-layer polypropylene (PP) is used as the separator, 1 M NaPF6 dissolved in DME is used as the electrolyte, and stainless steel shell is used as the outer shell to assemble into a CR2025 button cell.
[0087] (3) The half-cell assembled by the above process was heated at room temperature at 2 mA cm -2 The current density and 2 mAh cm -2 The reversibility test of electroplating and stripping was carried out under the condition of sodium deposition amount and charge cut-off voltage of 0.5 V. The results of the first week coulombic efficiency and average coulombic efficiency are shown in Table 2.
[0088] Table 2 First week coulombic efficiency and average coulombic efficiency of half-cell As can be seen from Table 2, the first cycle coulombic efficiency of the copper-based composite current collector modified by copper sulfide prepared in Examples 1-8 is about 90-98%, and the average coulombic efficiency is about 97.00-99.95%. The one prepared in Example 1 shows the best cycle performance.
[0089] Figure 7 The half-cell with Example 1-8 as the working electrode and sodium as the counter electrode at 2 mA cm -2 The current density and 2 mAh cm -2 Sodium deposition amount, coulombic efficiency cycle stability diagram under the condition of charging cut-off voltage of 0.5 V. It can be seen that when Examples 2-8 are used as current collectors, the coulombic efficiency fluctuates greatly, indicating that the reversibility of the deposition / stripping process of sodium metal is poor. However, when the current collector of Example 1 is used, the coulombic efficiency is very stable, and the average coulombic efficiency reaches more than 99.9%, indicating that the reversibility of sodium deposition and stripping is high and the loss of active sodium is small, indicating that the copper-based composite current collector modified by copper sulfide has the potential to be used in negative electrode-free sodium metal batteries.
[0090] The current collector of Example 1 was used at 2 mA cm -2 and 2 mAh cm -2The coulombic efficiency is very stable in the next cycle, and the average coulombic efficiency reaches more than 99.9%, indicating that the reversibility of sodium deposition / stripping is high and the loss of active sodium is small, indicating that the copper-based composite current collector modified by nanorod-shaped copper sulfide has the potential to be used in negative electrode-free sodium metal batteries. Figure 5 It can be seen from a that the copper-based composite current collector modified by copper sulfide prepared in Example 1 has a high conductivity at 2 mA cm -2 The current density and 2 mAh cm -2 Under the condition of sodium deposition, it can stably cycle for more than 700 cycles and has an average coulombic efficiency close to 100%. Figure 5 b It can be seen that the charge-discharge curve of the negative electrode-free current collector prepared in this application only shows the current collector properties. In the subsequent cycles, there is almost no capacity belonging to CuS, and only about 0.6% of the capacity exists in the first week.
[0091] In order to further explore the effect of copper sulfide-modified copper-based composite current collector on the dendrite inhibition and cycle life of sodium metal batteries when applied to sodium metal batteries, the following battery (symmetrical battery) was assembled and its performance was tested.
[0092] The sodium metal sheet was pressed onto the copper-based composite current collector modified with copper sulfide prepared in Example 1 as the working electrode and the counter electrode of the battery, respectively, and assembled into a button cell (symmetrical cell), and the dendrite inhibition effect and cycle life of the symmetrical cell were tested. The specific test process of the assembly and performance of the symmetrical cell is as follows: (1) The copper-based composite current collector modified with copper sulfide prepared in Example 1 was vacuum dried at 60° C. and cut into pieces with a diameter of 16 mm; (2) A sodium metal sheet (12 mm in diameter) is pressed onto the copper-based composite current collector modified with copper sulfide cut in the first step to prepare a pole piece; (3) The electrodes prepared in step (2) were used as the working electrode and the counter electrode, double-layer polypropylene (PP) was used as the diaphragm, 1 M NaPF6 dissolved in DGM was used as the electrolyte, and a stainless steel shell was used as the outer shell to assemble into a CR2025 button battery.
[0093] (4) The symmetrical battery assembled by the above process was subjected to the conditions of 4 mA cm -2 The current density is 4 mAhcm -2 Under the condition of sodium deposition, the dendrite inhibition and cycle life tests were carried out. The test results are as follows Figure 6 As shown in the figure, at a current of 4 mA cm -2 and high surface capacity 4 mAh cm -2In the next cycle, the symmetric batteries all achieved a stable cycle of more than 1000 hours. The sodium-philic copper sulfide layer effectively promoted the uniform distribution of sodium ions on the current collector, regulated the uniform nucleation and subsequent stable growth of sodium metal, inhibited dendrite growth and buffered volume expansion, indicating that the copper-based composite current collector modified by copper sulfide has the potential to be used in negative electrode-free sodium metal batteries.
[0094] In addition, the application of the copper-based composite current collector modified by copper sulfide prepared in Example 1 in a negative electrode-free magnesium battery was further explored, and the test results were as follows: Fig.10 As shown, at 1 mA cm -2 The current density and 1 mAh cm -2 With a magnesium deposition amount of 1.5477 W·m-1, it can stably cycle for 275 cycles (more than 500 h) with an average coulombic efficiency of up to 99.6%, proving its super practicality in negative electrode-free magnesium batteries.
[0095] Application Example 1 The copper-based composite current collector modified by copper sulfide prepared in Example 1 is used to prepare a negative electrode-free sodium metal battery, and the steps are as follows: (1) The positive electrode active material (sodium iron pyrophosphate), binder PVDF, and conductive agent Super P Li were dissolved in N-methylpyrrolidone solvent at a mass ratio of 8:1:1 and stirred evenly to prepare a slurry. The slurry was applied on the current collector and dried overnight at 120°C in vacuum. Then, a 12 mm pole piece was punched and the pole piece loading was 12 mg cm -2 .
[0096] (2) The copper-based composite current collector modified with copper sulfide prepared in Example 1 was punched into a pole piece (with a diameter of 16 mm), a double-layer polypropylene (PP) was used as a separator, 80 μL of 1 M electrolyte (sodium salt is sodium hexafluorophosphate (NaPF6)), and the organic solvent is ethylene glycol dimethyl ether (DME)) was added dropwise. A stainless steel shell was used as the outer shell to assemble a CR2025 button battery.
[0097] (3) The sodium metal battery assembled by the above process was subjected to charge and discharge tests at room temperature in the potential range of 1.5-3.9 V. The charge and discharge curves and cycle performance are shown in Figure 2. Figure 7 shown. Figure 7 It can be seen that at a current density of 0.5 C, the negative electrode-free sodium metal battery assembled with the copper-based composite current collector modified by copper sulfide prepared in Example 1 has a capacity retention rate of 98% and a coulombic efficiency of more than 99% after 90 stable cycles. Figure 7 It can be seen that the cycle stability is good, which proves that the loss of active substances in the positive electrode material is small and the active substances in the material are well maintained. This further confirms the application potential of the copper-based composite current collector modified by copper sulfide in Example 1 in negative electrode-free sodium metal batteries.
[0098] A negative electrode-free magnesium metal battery is prepared using the copper-based composite current collector modified by copper sulfide prepared in Example 1, and the steps are as follows: (1) The copper-based composite current collector modified with copper sulfide prepared in Example 1 was punched into a pole piece (with a diameter of 16 mm), a double-layer polypropylene (PP) was used as a separator, and 80 μL of 1 M electrolyte (magnesium salt is magnesium bis(trifluoromethylsulfonyl)imide (Mg(TFSI)2), and the organic solvent is tetrahydrofuran (THF)) was added dropwise. A stainless steel shell was used as the outer shell to assemble into a CR2025 button battery.
[0099] (3) The magnesium metal battery assembled by the above process was heated at room temperature and 1 mA cm -2 , 1 mA h cm -2 Under the condition of , the charge and discharge curves of the 1st, 5th, 10th, 15th and 20th cycles are as follows Figure 8 As shown in Figure 2, after 5 weeks of activation, the charge and discharge curves tend to be consistent. Under the same test conditions, Fig. 9 It shows a smooth time-voltage curve without obvious voltage fluctuation. After 125 cycles of the negative electrode-free sodium metal battery assembled with the copper sulfide-modified copper current collector prepared in Example 1, the Coulomb efficiency is still stable at more than 99.6%, with good cycle stability. This further confirms the application potential of the composite current collector in Example 1 in negative electrode-free sodium metal batteries. Finally, as Fig.10 As shown in the figure, the assembled anode-free magnesium battery has a -2 , 1 mA h cm -2 Under the condition of stable cycling for more than 275 cycles (500 h) and an average coulombic efficiency of up to 99.6%.
[0100] Application Example Comparative Example 1 The copper-based composite current collector prepared in Comparative Example 1 was used to prepare a negative electrode-free sodium metal battery, and the steps were as follows: (1) The positive electrode active material (sodium iron pyrophosphate), binder PVDF, and conductive agent Super P Li were dissolved in N-methylpyrrolidone solvent at a mass ratio of 8:1:1 and stirred evenly to prepare a slurry. The slurry was applied on the current collector and dried overnight at 120°C in vacuum. Then, a 12 mm pole piece was punched and the pole piece loading was 13 mg cm -2 Made into positive electrode sheet.
[0101] (2) The copper-based composite current collector prepared in Comparative Example 2 was punched into a pole piece (with a diameter of 16 mm), a double-layer polypropylene (PP) was used as a separator, 80 μL of 1 M electrolyte (sodium salt is sodium hexafluorophosphate (NaPF6)), and the organic solvent is ethylene glycol dimethyl ether (DME)) was added dropwise. A stainless steel shell was used as the outer shell to assemble a CR2025 button battery.
[0102] (3) The sodium metal battery assembled by the above process was charged and discharged at room temperature in the potential range of 1.5-3.9 V. Its cycle performance is as follows Figure 7 shown.
[0103] Figure 7 It can be seen that at a current density of 0.5 C, the discharge capacity of the negative electrode-free sodium metal battery assembled with the copper-based composite current collector prepared in Comparative Example 1 continued to decrease during the entire cycle, and the discharge capacity was reduced to 15 mAh g after 15 cycles. -1 In addition, its first-week discharge capacity is much lower than the theoretical capacity of the active material, and the capacity decays very quickly after 15 cycles of the battery, which proves that the active material of the positive electrode material is seriously lost.
[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A copper-based composite current collector, characterized in that: The copper-based composite current collector is prepared by in-situ constructing a copper sulfide layer with a linear structure having a diameter of 0.05-1 μm on the surface of a copper foil. The in-situ constructed thickness of the copper sulfide layer is 0.5-5 μm.
2. The method for preparing the copper-based composite current collector according to claim 1, characterized in that: The steps are: (1) Place the copper foil in an acidic solution to remove impurities on the surface of the copper foil; (2) Immerse the copper foil treated in step (1) in a sulfide solution, wash the soluble salt after the reaction is completed, repeat the immersion-washing operation, and obtain a copper-based composite current collector after drying.
3. The method for preparing the copper-based composite current collector according to claim 2, characterized in that: The acidic solution in step (1) is one or more of HCl solution, H2SO4 solution and CH3COOH solution.
4. The method for preparing the copper-based composite current collector according to claim 3, characterized in that: In step (2), the sulfide solution is a sodium sulfide solution or a potassium sulfide solution, and the concentration of sodium sulfide or potassium sulfide in the sulfide solution is 0.002-0.010 g / mL.
5. The method for preparing the copper-based composite current collector according to claim 4, characterized in that: The copper foil is immersed in the sulfiding solution for 10-300 s.
6. A negative electrode-free sodium / magnesium metal battery, characterized in that: The invention comprises a positive electrode, an electrolyte, a separator and the copper-based composite current collector according to claim 1.
7. The negative electrode-free sodium / magnesium metal battery according to claim 6, characterized in that: The positive electrode comprises a positive electrode current collector and a positive electrode film placed on the positive electrode current collector, wherein the positive electrode film comprises a positive electrode active material, a conductive agent and a binder; and the electrolyte comprises a sodium / magnesium salt and an organic solvent.
8. The negative electrode-free sodium / magnesium metal battery according to claim 6, characterized in that: When the negative electrode-free sodium / magnesium metal battery is a negative electrode-free sodium metal battery, the positive electrode active material is any one of sodium vanadium phosphate, sodium ferric pyrophosphate, sodium ferric pyrophosphate and sodium manganese ferric pyrophosphate; the binder is polyvinylidene fluoride or polytetrafluoroethylene; the sodium salt is any one or more of sodium hexafluorophosphate, sodium perchlorate, sodium trifluoromethylsulfonate, sodium tetrafluoroborate, sodium bis(fluorosulfonyl)imide and sodium bis(trifluoromethylsulfonyl)imide; the organic solvent is any one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, diethylene glycol dimethyl ether, 1,3-cyclopentanediol, ethylene glycol dimethyl ether and triethylene glycol dimethyl ether.
9. The negative electrode-free sodium / magnesium metal battery according to claim 6, characterized in that: When the negative electrode-free sodium / magnesium metal battery is a negative electrode-free magnesium metal battery, the positive electrode active material is MgCrMnO4 or MgV2O4; the binder is polyvinylidene fluoride or polytetrafluoroethylene; the magnesium salt is Mg(TFSI)2 or Mg(SO3CF3)2; and the organic solvent is tetrahydrofuran and / or ethylene glycol dimethyl ether.
10. The negative electrode-free sodium / magnesium metal battery according to claim 8 or 9, characterized in that: The conductive agent is any one or more of graphene, carbon nanotubes, acetylene black, Ketjen black and Super P Li; the separator is any one of polyethylene, polypropylene microporous membrane, glass fiber membrane and polyacrylonitrile separator.
Citation Information
Patent Citations
Preparation method of negative current collector of negative-electrode-free sodium ion battery
CN117878259A
Cited By
Copper current collector for in-situ construction of three-dimensional structure coupling solid electrolyte boundary phase on surface and preparation method and application of copper current collector
CN121011610A
A copper current collector with a three-dimensional structure coupled solid electrolyte interface phase constructed in-situ on a surface and a preparation method and application thereof
CN121011610B